CFD Numerical simulations of Francis turbines - Laín-Beatove, Santiago; García.Ruiz, Manuel J.; Quintero-Arboleda, Brian; Orrego-Bustamante, Santiago (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
In this paper the description of the internal flow in a Francis turbine is addressed from a numerical point of view. The simulation methodology depends on the objectives. On the one hand, steady simulations are able to provide the hill chart of the turbine and energetic losses in its components. On the other hand, unsteady simulations are required to investigate the fluctuating pressure dynamics and the rotor-stator interaction. Both strategies are applied in this paper to a working Francis turbine in Colombia. The employed CFD package is ANSYS-CFX v. 11. The obtained results are in good agreement with the in site experiments, especially for the characteristic curve.